Efficiency of Using Built-In Bundles of Cogeneration Steam Turbine Condensers for Make-up Water Heating - Shempelev A.G.; Suvorov D.M.; Iglin P.V. (Problems of the Regional Energetics)
The purpose of the study is to determine the conditions and efficiency of the use of built-in bundles of condensers of cogeneration steam turbines for make-up water heating during their work when the main bundles are disabled. The proposed method for estimating the heat flows entering the condenser when working with a closed sliding grid is used. The program of the thermal calculation program for steam turbine condensers and a computational mathematical model of a turbine plant type T-50-130 are applied. The heat fluxes entering the condenser were calculated in a wide range of influencing factors. An important result of the calculations is the identification of significant limitations of the applicability of this method of the make-up water heating according to the condition that the temperature of the make-up water at the exit from the built-in bundle is not exceeded. Calculation studies on the mathematical model of a condenser to determine the pressure in the condenser depending on the pressure in the lower heat extraction section with different levels of throughput of the closed sliding grid and different flow rates of the make-up water were carried out. Another result is a calculated estimate of the energy efficiency when using built-in bundles for heating the make-up water. It was found that heat saving in the considered modes always takes place, and when working on a heat mode, it is close to the heat load of the built-in bundles, and when working on an electric mode, it is several times lower.